Addendum to "violating the string winding number maximally in anti-de Sitter space" - Giribet, Gaston Enrique (2017)
We revisit the computation of maximally winding violating string amplitudes in three-dimensional anti-de Sitter space discussed in Ref. G. Giribet, Violating the string winding number maximally in anti-de Sitter space, Phys. Rev. D 84, 024045 (2011)PRVDAQ1550-799810.1103/PhysRevD.84.024045. Here, we give an alternative derivation of these observables. This derivation, the simplest to the best of our knowledge, follows from identities between spectrally flowed representations of sl^(2)k Kac-Moody algebra and, in contrast to G. Giribet, Violating the string winding number maximally in anti-de Sitter space, Phys. Rev. D 84, 024045 (2011)PRVDAQ1550-799810.1103/PhysRevD.84.024045, it does not resort to conjugate representations with auxiliary fields, but it rather involves the standard Wakimoto free field representation.